Handbook of solid waste management and waste minimization technologies - Cheremisinoff, Nicholas P. (Butterworth-Heinemann, 2003)
This Handbook is an essential tool for plant managers, process engineers, environmental consultants, and site remediation specialists that focuses on practices for handling a broad range of industrial solid waste problems. In addition to equipment and process options, the author presents information on waste minimization practices that can be used in conjunction with or can provide alternatives to equipment and process investments. Environmental cost accounting measures and energy-efficient technologies are provided. Valuable information for those concerned with meeting government regulations and with the economic considerations (such as fines for violations and cost-effective methods) is presented in a practical manner. Included in the text are sidebar discussions, questions for thinking and discussion, recommended resources for the reader (including Web sites), and a comprehensive glossary. Two companion books by Cheremisnoff are available: Handbook of Water and Wastewater Treatment Technologies, and Handbook of Air Pollution Control Technologies. - Covers leading edge technology and standard equipment for managing industrial solid waste problems - Valuable in meeting government regulations - Presents in-depth analysis of the financial impact of alternative technologies available.
Keywords: Refuse and refuse disposal.; Waste minimization.; elektronické knihy; electronic books